Evaluasi Kebijakan Pemerintah Dalam Penyelenggaraan Pendidikan Agama Islam - Muhammad Idrus (EL-TARBAWI, 2014)
The current paper critisizes government’s policy on Islamic religion education implementation, in term of the organizer/ administrator and subject matters. Government Regulation (Peraturan Pemerintah) No 55/2007 explicitly explained about how Islamic religion education and other religions education organized and administered. This paper found that the regulation has several critical points on its implementation, organization, and administration. Therefore, it is urgent for Ministry of Religious Affair and Ministry of Education to make synergic cooperation on implementing Islamic religion education development, whether on its education system, infrastructures, subject materials, and human resource development. If this cooperation appears to be hard to implement, Ministry of Religious Affair better to return its role in managing Islamic education to Ministry of Education. Means, this paper recommends the government to revise the regulation on religions education system.